Imaging before transfer to designated pediatric trauma centers exposes children to excess radiation. Issue 2 (August 2016) - Puckett, Yana; Bonacorsi, Louis; Caley, Matthew; Farmakis, Shannon; Fitzpatrick, Colleen; Chatoorgoon, Kaveer; Greenspon, Yosef; Vane, Dennis W.
Abstract : BACKGROUND: Pediatric trauma patients transferred to pediatric trauma centers (PTCs) often have imaging at the originating hospital (OH). The increased use of computed tomography (CT) raises concerns about malignancy risk from ionizing radiation leading many PTCs to adopt radiation dose reduction strategies. We hypothesized that pediatric trauma patients are exposed to excess radiation from imaging before transfer. METHODS: A retrospective review of 1, 383 scans was performed on all trauma patients with CT imaging before transfer to our Level I PTC from 2010 to 2014. Demographics, type of imaging, necessity for repeat imaging, appropriateness of imaging, and radiation dose delivered were recorded. Comparative radiation dosing was calculated using the dose-length product (DLP [expressed in mGy-cm]). All CT scans except for CT of the abdomen and pelvis and CT of the head were excluded for complete DLP data issues. Scans were considered clinically appropriate if they met Advanced Trauma Life Support (ATLS) recommendations (ATLS+) and not indicated if they did not meet ATLS criteria (ATLS−). Some scans were repeated because of technical issues. Median ΔDLP represents the difference in dose patients received at OH versus at PTC. RESULTS: A total of 673 patients were analyzed. Average age was 11 years, and 65.4% were male. Mean DLP at PTC was 54% lower for all analyzed scans compared with OH ( p < 0.0001). DLP at PTC was 51% lower for CT of the abdomen and pelvis and 62% lower for CT of the head. Children received excess dose of 578.62 mGy-cm for scans at OH that were unnecessary. For ATLS+ imaging, children received a median excess of 444.42 mGy-cm of radiation at OH than they would have received had the scans been performed at PTCs using pediatric radiation reduction strategies. CONCLUSION: Pediatric trauma imaging performed at transferring institutions often does not adhere to ATLS recommendations and exceeds required ionizing radiation dosages. This study further confirms ATLS recommendations supporting prompt patient transfer without delay for imaging. LEVEL OF EVIDENCE: Therapeutic study, level IV.